A Preobrazsenszkij-Buharin vita ürügyén egy kikényszerített fázisátmenet szcenáriói - Barancsuk, János (Közép-Európai Közlemények, 2015)
In our research we would like to lay out the skeleton of a possible but quite exotic interpretation of the aspirations to build up the socialism’s social-economical form, according to the Soviet “mechanism debates” from the 1920s. The specialty of our approach is that we think of the “modernising” experiment of making radical changes in the working mechanism of the national economy as the visibility of a persuasive intent of a peculiar institutional “phase transition”. Throughout the research we used the chaos and network theory’s conceptual and methodical set aside with the regular methodical elements. We hope that our novel approach gives an opportunity to expand on analogies and to assign research goals which will enrich the literature on analyses of the planned economy’s unsuccessful implementations with further data.